2006
DOI: 10.1093/humrep/del039
|View full text |Cite
|
Sign up to set email alerts
|

Non-genetic and non-gestational parenthood: consequences for parent-child relationships and the psychological well-being of mothers, fathers and children at age 3

Abstract: It appears that the absence of a genetic and/or gestational link between parents and their child does not have a negative impact on parent-child relationships or the psychological well-being of mothers, fathers or children at age 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
100
2
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(118 citation statements)
references
References 19 publications
7
100
2
9
Order By: Relevance
“…De meeste artikelen of publicaties die geschreven zijn over commercieel draagmoederschap betreffen de intentie en ervaring van de draagmoeder (Ciccarelli & Beckman, 2005). Er is een aantal empirische studies van de onderzoekers Golombok (Golombok, Murray, Jadva, MacCallum, & Lycett, 2004;Golombok, MacCallum, Murray, Lycett, & Jadva, 2006a;Golombok et al, 2006b) en MacCallum (MacCallum, Lycett, Murray, Jadva, & Golombok, 2003). Deze studies hebben echter betrekking op zeer jonge kinderen en betreft draagmoederschap begeleid door professionele overheidsinstanties.…”
Section: De Pedagogische Gevolgen Van Draagmoederschapunclassified
“…De meeste artikelen of publicaties die geschreven zijn over commercieel draagmoederschap betreffen de intentie en ervaring van de draagmoeder (Ciccarelli & Beckman, 2005). Er is een aantal empirische studies van de onderzoekers Golombok (Golombok, Murray, Jadva, MacCallum, & Lycett, 2004;Golombok, MacCallum, Murray, Lycett, & Jadva, 2006a;Golombok et al, 2006b) en MacCallum (MacCallum, Lycett, Murray, Jadva, & Golombok, 2003). Deze studies hebben echter betrekking op zeer jonge kinderen en betreft draagmoederschap begeleid door professionele overheidsinstanties.…”
Section: De Pedagogische Gevolgen Van Draagmoederschapunclassified
“…With respect to the families that used gestational surrogacy, compared to families that received sperm or eggs, studies coincide in indicating that they are the group that is most open to disclosure, given that, in contrast to other techniques of assisted procreation, it is not possible to hide the surrogate gestation, as the mother does not experience the pregnancy and the parents have to explain the arrival of their children to everyone else (Blyth 1995;MacCallum et al 2003;Golombok et al 2004;Golombok et al 2006a;Golombok et al 2006b;Jadva 2012). 1 A second issue that appears in the research, although less developed, concerns the strategies followed when narrating these origins, that is, how families imagine, plan, and put this revelation into practice.…”
Section: Isabel Jociles Ana M Rivas and Consuelo áLvarez Introdumentioning
confidence: 99%
“…To date, most of the study populations relating to oocyte donation have been recipients of anonymous donation whose children have been aged up to eight years (Pettee and Weckstein, 1993;Weil et al, 1994;Söderström-Anttila et al, 1998;Baetens et al, 2000;Hahn and CraftRosenberg, 2002;Greenfeld and Klock, 2004;Klock and Greenfeld, 2004;Golombok et al, 2004Murray et al, 2006;Mac Dougall et al, 2007;van Berkel et al, 2007;Laruelle et al, 2012), although one recent Finnish study has included parents of children aged up to 14 years (Söderström-Anttila et al, 2010). These studies have revealed intended disclosure rates of between 26 and 81%, although not all parents indicating an intention to disclose will necessarily do so Golombok et al, 2006;Murray et al, 2006;Mac Dougall et al, 2007;van Berkel et al, 2007), and only three studies have included longitudinal data tracking parental disclosure behaviour. One of these was undertaken in Finland (Söderström-Anttila et al, 1998, 2010 and two the UK (Golombok et al, 1999;Murray et al, 2006) and (Golombok et al, 2004;Readings et al, 2011).…”
Section: Introductionmentioning
confidence: 99%